Class I histone deacetylase inhibition promotes CD8 T cell activation in ovarian cancer. (24th December 2020) - McCaw, Tyler R.; Goel, Nidhi; Brooke, Dewey J.; Katre, Ashwini A.; Londoño, Angelina I.; Smith, Haller J.; Randall, Troy D.; Arend, Rebecca C.
Abstract: Objective: Patients with epithelial ovarian cancer (EOC) typically present with late‐stage disease, posing a significant challenge to treatment. Although taxane and platinum‐based chemotherapy plus surgical debulking are initially effective, EOC is marked by frequent recurrence with resistant disease. Immunotherapy represents an appealing treatment paradigm given the ability of immune cells to engage metastatic sites and impede recurrence; however, response rates to checkpoint blockade in ovarian cancer have been disappointing. Here, we tested whether class I HDAC inhibition can promote anti‐tumor T cell responses in a spontaneous and nonspontaneous murine model of EOC. Methods: We used the spontaneous Tg‐MISIIR‐Tag and nonspontaneous ID8 models of murine ovarian cancer to test this hypothesis. Whole tumor transcriptional changes were assessed using the nCounter PanCancer Mouse Immune Profiling Panel. Changes in select protein expression of regulatory and effector T cells were measured by flow cytometry. Results: We found that treatment with the class I HDAC inhibitor entinostat upregulated pathways and genes associated with CD8 T cell cytotoxic function, while downregulating myeloid derived suppressor cell chemoattractants. Suppressive capacity of regulatory T cells within tumors and associated ascites was significantly reduced, reversing the CD8‐Treg ratio. Conclusions: Our findings suggest class I HDAC inhibition can promote activation of intratumoral CD8 T cells, potentially by compromising suppressive networks within the EOC tumor microenvironment. In this manner, class I HDAC inhibition might render advanced‐stage EOC susceptible to immunotherapeutic treatment modalities. Abstract : Expression of genes corresponding to CD8 T cell activation and effector function are upregulated following entinostat treatment. Class I HDAC inhibition also compromises the intratumoral suppressive network at multiple nodes in epithelial ovarian cancer. Accordingly, class I HDAC inhibition can be integrated into current treatment strategies to promote endogenous anti‐tumor immune responses and sensitize ovarian cancer to immunotherapy.